Dekonstruksi Epistemik Investasi Sosial dalam Bayang-Bayang Neoliberalisme : Kritik terhadap Rasionalitas Tekno-Birokratis Kebijakan Kesejahteraan di Kabupaten Bima - Wawan Mulyawan; Muhamad Lutfi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to deconstruct the technocratic rationality underpinning social investment policies implemented in Bima Regency by critically illuminating the ideological co-optation of neoliberalism, which manifests through the language of modernity, productivity, and pseudo-empowerment. Within a structurally asymmetrical and historically marginalized context, the global paradigm of social investment has been adopted in an ahistorical and depoliticized manner, resulting in policy architectures that are both irrelevant and exclusionary. Employing a critical-qualitative approach with a deconstructive design rooted in post-structuralist epistemology, this research conceptualizes public policy as an ideological text that demands reinterpretation and recontextualization. Data were obtained through rigorous analysis of institutional and academic literature and interpreted using the framework of Critical Discourse Analysis (CDA). The findings reveal that social investment policies in Bima function not as instruments of structural transformation but rather as symbolic mechanisms of ideological co-optation, which conceal systemic inequality under the guise of bureaucratic performance metrics. The local state apparatus has lost its articulative capacity, subordinated to a global epistemology that is profoundly indifferent to local particularities. Terminologies such as “empowerment” and “human capacity” are reduced to administrative slogans devoid of redistributive justice. Consequently, the social investment paradigm has shifted the state's role from an agent of justice to a managerial entity of poverty normalizing exclusion and reinforcing the subordination of the subaltern populace.